La Russia e l'Occidente = Россия и Запад : atti della Giornata di studio : Napoli, 9 giugno 2022 Autori - Cigliano, Giovanna; Tagliaferri, Teodoro (Scuola delle Scienze Umane e Sociali. Quaderni, 2023)
At various junctures in the contemporary age, the relationship between Russia and the West has occupied a crucial place in the debates of Russian intellectual and political elites about the peculiar path and historical destiny of their country, constituting at the same time an important factor in Europe's cultural self-definition, geohistorical contours, security system. The outbreak of the Russian-Ukrainian war has invested a question that had already become "classic" with a renewed, urgent topicality. The essays collected in the volume range over the time span from the final decades of the Tsarist Empire to the present day, focusing on topics such as Nikolai Danilevsky's influential reflection on Rossiia i Evropa (A. Venturi), Max Weber's analysis of Russian constitutionalism in 1905-07 (F. Fera), the pro-Westerner elements in Russian nationalism at the beginning of the twentieth century (G. Savino), the contribution of Russian emigration to the conceptualization of the West/East cleavage in the interwar period (R. Gravina), the Soviet Union in the vision of A.J. Toynbee (T. Tagliaferri), the "Ukrainian question" between the 20th and 21st centuries (R. Valle), the competition over the post-Soviet space between the Russian Federation and the European Union (M. Puleri). In the introduction, G. Cigliano dwells on the recent aspects of the relationship between Russia, Europe and the West which seem more suitable for interpreting the roots of the ongoing conflict in a historical-historiographical perspective.